Culture, Revolution and Hegemony: Review of La isla gigante: Cuba y su cultura contemporánea. Principales vínculos con América Latina (1959-2016), by Antonio Álvarez Pitaluga - Barboza Núñez, Esteban (2020)
The book reviewed here centers its analysis on the cuban cultural production from the triumph of the Cuban Revolution to the present. Making use of the concept of cultural hegemony from Gramsci, this text shows how the relationship between culture and politics has been delevoped on the cuban context, which have been its points of encounter and which have been its discrepancies. The book’s historical analysis shows how the cultural production has played a role of a source of power in the political and social life of Cuba, and how the different types of artists have performed as organic intelectuals on the cultural life of the island.